The Obligation Of Local Content Requirements (Lcr) Of Power Plant From The Perspective Of The World Trade Organization (WTO) - Nurhayati, Muzdalifah Mei (Unram Law Review, 2023)
As a developing country, Indonesia requires foreign investments, particularly to improve the welfare of its people. Trade provisions are regulated by the World Trade Organization (WTO) mainly to reduce all potential barriers that emerge in the global investment realm. Along with the entry of various foreign products and investments, developing countries often apply local content requirements, which in Indonesian terms are known as the Tingkat Komponen Dalam Negeri (TKDN). Particularly in the field of electricity infrastructure development, the government of Indonesia regulates the minimum level of TKDN in the construction of power plants. The TKDN provisions normatively conflict with WTO principles, namely national treatment, because they are included in the illustrative list regulated in the Agreement on Trade-Related Investment Measures (TRIMS). In this article, the author uses a normative research method in which research is conducted by examining Indonesian TKDN regulations related to the construction of power plants against the WTO agreement for a more in-depth analysis. Â This article aims to examine whether the TKDN provisions made by the Indonesian government are parallel with the WTO policies. It can be concluded that Indonesia's TKDN policy could violate WTO provisions. Still, if the TKDN policy is for the welfare of the community and managed directly by the government, it could be excluded since it is conducted not within purely commercial profits purposes.